Al Ibtikar fi Wasaail Ta'allum al Lughah al 'Arabiyyah fi al 'Ashr al Raqmiy: Video Animasi kahillin li Ta'ziz Mahaarah al Istima' Laday al Thullab bi al Madrasah al Tsanawiyah al islamiyyah al Hukumiyyah al Uulaa Pasuruan - Rozaq, Roihan Sabila; Machmudah, Umi; Yurisa, Penny Respati (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
Arabic language learning, especially in listening material, is not optimal due to the lack of maximum media use. Most teachers only rely on the material in the book. This study aims to make animated video media on Arabic listening material and explain the effectiveness for MAN 1 Pasuruan students. This type of research is a development guided by the 4D development model. The subjects of this study were two people from linguists and media experts, 64 students. Data collection methods were questionnaires, observations, interviews, and tests. Data were analyzed using the mean formula to find the media's average score of validity and practicality. The results showed that the Arabic animated video media obtained a validity score of 92% from linguists and 93% from media experts. The practicality score from students was 86%. The N-Gain test results show the average post-test value for the experimental class using animated video media for listening to Arabic language is 0.71. The results of the independent sample t-test showed a Sig. (2-tailed) of 0.00039 < 0.05. It can be stated that Ho is rejected and Hl is accepted. It can be concluded that the animated video on listening material that has been developed is effective in improving Arabic listening skills for MAN 1 Pasuruan students